Dachsous1–Fat4 Signaling Controls Endothelial Cell Polarization During Lymphatic Valve Morphogenesis—Brief Report. Issue 9 (September 2017) - Pujol, Francoise; Hodgson, Tina; Martinez-Corral, Ines; Prats, Anne-Catherine; Devenport, Danelle; Takeichi, Masatoshi; Genot, Elisabeth; Mäkinen, Taija; Francis-West, Philippa; Garmy-Susini, Barbara; Tatin, Florence
Abstract : Objective—: The purpose of this study was to investigate the role of Fat4 and Dachsous1 signaling in the lymphatic vasculature. Approach and Results—: Phenotypic analysis of the lymphatic vasculature was performed in mice lacking functional Fat4 or Dachsous1 . The overall architecture of lymphatic vasculature is unaltered, yet both genes are specifically required for lymphatic valve morphogenesis. Valve endothelial cells (Prox1 high [prospero homeobox protein 1] cells) are disoriented and failed to form proper valve leaflets. Using Lifeact-GFP (green fluorescent protein) mice, we revealed that valve endothelial cells display prominent actin polymerization. Finally, we showed the polarized recruitment of Dachsous1 to membrane protrusions and cellular junctions of valve endothelial cells in vivo and in vitro. Conclusions—: Our data demonstrate that Fat4 and Dachsous1 are critical regulators of valve morphogenesis. This study highlights that valve defects may contribute to lymphedema in Hennekam syndrome caused by Fat4 mutations. Abstract : Supplemental Digital Content is available in the text.